Are all outcomes in chronic heart failure rated equally? An argument for a patient-centred approach to outcome assessment - Chang, Sungwon; Newton, Phillip; Inglis, S.; Luckett, T.; Krum, H.; Macdonald, P.; Davidson, Patricia (Springer New York LLC, 2014)
Chronic heart failure (CHF) is a multi-dimensional and complex syndrome. Outcome measures are important for determining both the efficacy and quality of care and capturing the patient’s perspective in evaluating the outcomes of health care delivery. Capturing the patient’s perspective via patient-reported outcomes is increasingly important; however, including objective measures such as mortality would provide more complete account of outcomes important to patients. Currently, no single measure for CHF outcomes captures all dimensions of the quality of care from the patient’s perspective. To describe the role of outcome measures in CHF from the perspective of patients, a structured literature review was undertaken. This review discusses the concepts and methodological issues related to measurement of CHF outcomes. Outcome assessment at the level of the patient, provider and health care system were identified as being important. The perspectives of all stakeholders should be considered when developing an outcomes measurement suite to inform CHF health care. This paper recommends that choice of outcome measures should depend on their ability to provide a comprehensive, comparable, meaningful and accurate assessment that are important to patient.